Entrepreneurship Education- Supporting Youth Employability for Effective Contribution to the Economy - Ibrahim, Afifa; Mufeed Ahmad, Prof. (Dr) S. (IJRDO - Journal of Business Management, 2017)
Today, India is one of the youngest nations in the world with more than 62% of its population in the working age group (15-59 years), and more than 54% of its total population below 25 years of age. This is a promising figure that can be a challenge as well as a huge opportunity. To reap this demographic dividend which is expected to last for next 25 years, we need to equip our workforce with employable skills and knowledge so that they can contribute substantively to the economic growth of the country. Taking a look at our global competition, our graduates need the skills attributes and capabilities to enable them to be successful in the ever changing global environment and thus help them meet the increasing demand from employers who want innovative, adaptable, resilient and flexible graduates who have an enterprising mind set. It is nevertheless important to say that entrepreneurial education is the need of the hour to support employability quotient of students thereby making effective contributions to the economy and society. Enterprise education clearly links to employability and as such should be at the core of Higher Education strategies. When Universities and colleges promote employability they are also promoting elements of entrepreneurship. The world is moving fast and long term challenges of globalisation are seem to be intensifying. The present study strives to identify, through extensive literature and secondary data, various challenges that are faced by higher education institutions while imparting entrepreneurial education and the critical nature of embedding enterprise education in graduate curriculum for enhancing and supporting employability. The challenges when dealt with vigour can help youth, in a long way to become products of smart, sustainable and inclusive economy delivering high levels of employment, productivity and social cohesion.